2006
DOI: 10.1073/pnas.0609638103
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid of the prion domain of Sup35p has an in-register parallel β-sheet structure

Abstract: The [PSI ؉ ] prion of Saccharomyces cerevisiae is a self-propagating amyloid form of Sup35p, a subunit of the translation termination factor. Using solid-state NMR we have examined the structure of amyloid fibrils formed in vitro from purified recombinant Sup35 1-253 , consisting of the glutamine-and asparagine-rich Nterminal 123-residue prion domain (N) and the adjacent 130-residue highly charged M domain. Measurements of magnetic dipole-dipole couplings among 13 C nuclei in a series of Sup35NM fibril samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
302
2
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 272 publications
(334 citation statements)
references
References 62 publications
27
302
2
3
Order By: Relevance
“…With single-site labeling, the dipolar recoupling data represent measurements of intermolecular distances, which can readily distinguish parallel from antiparallel β-sheets and establish the precise registry of backbone hydrogen bonds within the β-sheets. We have previously used 13 C fpRFDR-CT measurements to investigate β-sheet structures in fibrils formed by β-amyloid peptides (17,19,21) and by yeast prion proteins (18,63). Figure 10 compares experimental 13 C fpRFDR-CT data for AMY04 fibrils with simulations for ideal linear chains of 13 C nuclei with various internuclear spacings.…”
Section: Evidence For In-register Parallel β-Sheetsmentioning
confidence: 99%
See 2 more Smart Citations
“…With single-site labeling, the dipolar recoupling data represent measurements of intermolecular distances, which can readily distinguish parallel from antiparallel β-sheets and establish the precise registry of backbone hydrogen bonds within the β-sheets. We have previously used 13 C fpRFDR-CT measurements to investigate β-sheet structures in fibrils formed by β-amyloid peptides (17,19,21) and by yeast prion proteins (18,63). Figure 10 compares experimental 13 C fpRFDR-CT data for AMY04 fibrils with simulations for ideal linear chains of 13 C nuclei with various internuclear spacings.…”
Section: Evidence For In-register Parallel β-Sheetsmentioning
confidence: 99%
“…Measurements of 13 C-13 C and 15 N-15 N nuclear magnetic dipole-dipole couplings (which are proportional to the inverse cube of internuclear distances) were carried out with the constanttime fpRFDR (fpRFDR-CT) technique, as previously described (54) and applied to other amyloid-forming peptides and proteins (17,18,21,63), using 20 kHz MAS frequencies and 15 μs fpRFDR π pulses. In 15 N-15 N distance measurements, designed to probe the peptide backbone conformation at sites where uniformly labeled residues occurred sequentially, spin polarization was transferred from backbone 15 N nuclei to directly bonded 13 C α nuclei for signal detection using a transferred echo double resonance (TEDOR) sequence (64,65) after the 15 N fpRFDR-CT period, as previously described (66).…”
Section: Solid State Nmrmentioning
confidence: 99%
See 1 more Smart Citation
“…Using solid-state NMR, amyloids of the Alzheimer's A␤ peptide and the diabetes-associated amyloid peptide amylin are inregister parallel ␤-sheets (identical residues of different molecules aligned along the fiber long axis) (20)(21)(22) (23)(24)(25). Electron spin resonance studies showed in-register parallel ␤-sheet structures of amylin (26), ␣-synuclein (Parkinson's disease) (27), and Tau (Alzheimer's disease and other 'tauopathies') (28).…”
mentioning
confidence: 99%
“…34). Solid-state NMR studies of amyloids of the prion domains of Sup35 (35) and Ure2p (36) as well as Ure2p 10 -39 (37) have shown that each is a parallel, in-register ␤-sheet structure, meaning that, for example, residue 35 of one molecule is aligned opposite residue 35 of the preceding molecule and the subsequent molecule in the fibril.…”
mentioning
confidence: 99%